Complex calcium carbonate/polymer microparticles as carriers for aminoglycoside antibiotics. Issue 41 (27th June 2018) - Racovita, Stefania; Vasiliu, Ana-Lavinia; Bele, Adrian; Schwarz, Dana; Steinbach, Christine; Boldt, Regine; Schwarz, Simona; Mihai, Marcela
Abstract : Self-assembled microparticles of CaCO3 and pectin/polyelectrolyte complexes as carriers for streptomycin and kanamycin sulfates by transformation into calcium phosphates. Abstract : Composite microparticles of CaCO3 and two pectin samples (which differ by the functional group ratio) or corresponding nonstoichiometric polyelectrolyte complexes with different molar ratios (0.5, 0.9 and 1.2) are obtained, characterized and tested for loading and release of streptomycin and kanamycin sulphate. The synthesized carriers were characterized before and after drug loading in terms of morphology (by SEM using secondary electron and energy selective backscattered electron detectors), porosity (by water sorption isotherms) and elemental composition (by elemental mapping using energy dispersive X-ray and FTIR spectroscopy). The kinetics of the release mechanism from the microparticles was investigated using Higuchi and Korsmeyer–Peppas mathematical models.